Treatment With Resveratrol Ameliorates Mitochondrial Dysfunction During the Acute Phase of Status Epilepticus in Immature Rats - Folbergrová, Jaroslava (Front Neurosci, 2021)
The aim of the present study was to elucidate the effect of resveratrol (natural polyphenol) on seizure activity, production of ROS, brain damage and mitochondrial function in the early phase of status epilepticus (SE), induced in immature 12 day-old rats by substances of a different mechanism of action (Li-pilocarpine, DL-homocysteic acid, 4-amino pyridine, and kainate). Seizure activity, production of superoxide anion, brain damage and mitochondrial function were assessed by EEG recordings, hydroethidium method, FluoroJadeB staining and Complex I activity measurement. A marked decrease of complex I activity associated with the acute phase of SE in immature brain was significantly attenuated by resveratrol, given i.p. in two or three doses (25 mg/kg each), 30 min before, 30 or 30 and 60 min after the induction of SE. Increased O(2)(.–) production was completely normalized, brain damage partially attenuated. Since resveratrol did not influence seizure activity itself (latency, intensity, frequency), the mechanism of protection is likely due to its antioxidative properties. The findings have a clinical relevance, suggesting that clinically available substances with antioxidant properties might provide a high benefit as an add-on therapy during the acute phase of SE, influencing also mechanisms involved in the development of epilepsy.